Beyond blunts: reasons for cigarette and cigar use among African American young adult dual users. (3rd September 2018) - Mead, Erin L.; Lindstrom Johnson, Sarah; Siddiqui, Junaed; Butler, James; Kirchner, Thomas; Feldman, Robert H.
Abstract: Background: African American young adults are at high risk for dual use of cigarettes and cigars. Limited work has explored and characterized the reasons for use in this population and their relative importance for initiation and current smoking of these products. Method: Reasons for cigarette and cigar use were systematically explored and categorized using a mixed methods participatory approach called concept mapping. A series of in-person group sessions were held with 30 African American young adult (ages 18–29) current smokers of both cigarettes and cigars in Prince George's County, MD and Washington, DC. Participants brainstormed, sorted, rated, and interpreted their reasons for initiation and past 30-day use of cigarettes and cigars. A cluster map was generated using multi-dimensional scaling, and t-tests were used to explore differences in ratings by background characteristics. Results: Participants generated 64 reasons for smoking cigarettes and cigars, and categorized these reasons into six groups: emotions, urges, access, product characteristics, lifestyle, and outside pressure. Emotions and urges were the most important motivations for initiation and current smoking of both products. Product characteristics were significantly more important for cigar initiation and smoking than for cigarettes, and outside pressure was more important for current smoking of cigars than cigarettes. Ratings differed by gender, socioeconomic status, and smoking characteristics. Conclusions: Cigarette and cigar smoking have several overlapping motivations, but key differences were also found, most notably for product characteristics. The FDA's regulation of cigars and cigarettes should focus on addressing key characteristics appealing to young adults to curb dual use.